Brief telephone-delivered cognitive-behavioral therapy targeted to parents of children with functional abdominal pain: a randomized controlled trial - Levy, Rona L. (Pain, 2017)
Pediatric functional abdominal pain disorders (FAPD) are associated with increased healthcare utilization, school absences, and poor quality of life (QoL). Cost-effective and accessible interventions are needed. This multi-site study tested the effects of a 3-session cognitive-behavioral intervention delivered to parents, in person or remotely, on the primary outcome of pain severity and secondary outcomes (process measures) of parental solicitousness, pain beliefs, catastrophizing, and child-reported coping. Additional outcomes hypothesized a priori and assessed included functional disability, quality of life, pain behavior, school absences, healthcare utilization, and gastrointestinal symptoms. The study was prospective and longitudinal (baseline, 3 and 6 months follow-up) with three randomized conditions: social learning and cognitive-behavioral therapy in-person (SLCBT) or by phone (SLCBT-R) and education/support condition by phone (ES-R). Participants were children aged 7–12 with FAPD and their parents (N = 316 dyads). While no significant treatment effect for pain severity was found, the SLCBT groups showed significantly greater improvements compared to controls on process measures of parental solicitousness, pain beliefs and catastrophizing, and additional outcomes of parent-reported functional disability, pain behaviors, child healthcare visits for abdominal pain, and (remote condition only) quality of life and missed school days. No effects were found for parent and child-reported gastrointestinal symptoms, or child-reported quality of life or coping. These findings suggest that for children with FAPD, a brief phone SLCBT for parents can be similarly effective as in-person SLCBT in changing parent responses and improving outcomes, if not reported pain and symptom report, compared to a control condition.